New species of Chimarrhodella from Venezuela and Ecuador (Trichoptera: Philopotamidae) - Blahnik, Roger J. (Zootaxa, 2004)
Two new species of Chimarrhodella (Trichoptera: Philopotamidae) are described and placed within the current phylogenetic framework for the genus. New species described (with their corresponding distribution) are Chimarrhodella paria (Venezuela) and C. ornata (Ecuador).